2004
DOI: 10.1103/physrevlett.92.074801
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond and Subfemtosecond X-Ray Pulses from a Self-Amplified Spontaneous-Emission–Based Free-Electron Laser

Abstract: We propose a novel method to generate femtosecond and sub-femtosecond photon pulses in a freeelectron laser by selectively spoiling the transverse emittance of the electron beam. Its merits are simplicity and ease of implementation. When the system is applied to the Linac Coherent Light Source, it can provide x-ray pulses the order of 1 femtosecond in duration containing about 10 10 transversely coherent photons. † Emma@SLAC.Stanford.edu ‡ On leave from Deutches Elektronen Synchrotron (DESY),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
248
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 314 publications
(248 citation statements)
references
References 8 publications
0
248
0
Order By: Relevance
“…Although further consideration is necessary, the TCDP operation combined with various methods of attosecond pulse generation [26][27][28][29][30] will make it feasible to study ultrafast phenomena, including coherent X-ray Raman scattering or hard X-ray atomic lasers, at an attosecond scale.…”
Section: Discussionmentioning
confidence: 99%
“…Although further consideration is necessary, the TCDP operation combined with various methods of attosecond pulse generation [26][27][28][29][30] will make it feasible to study ultrafast phenomena, including coherent X-ray Raman scattering or hard X-ray atomic lasers, at an attosecond scale.…”
Section: Discussionmentioning
confidence: 99%
“…The magnetic compression with a slit between the second and third dipoles of a chicane was initially proposed by Borland to generate 10-20 fs long electron bunches at the Advanced Photo Source (APS) Linac [62]. Recently, it has been demonstrated that this technique can be used for the generation of ultra-short FEL pulses at SLAC and FERMI [60,[63][64][65]. The adaption of this system to produce sub-fs bunches is not trivial.…”
Section: Beam Collimation In a Dispersive Regionmentioning
confidence: 99%
“…Even shorter X-ray pulses are desired for some scientific experiments such as biomolecular imaging 14 and time-resolved pump-probe spectroscopy in femtochemistry 40 . At the LCLS, two experimental methods-a low-charge (20 pC) mode 41 and a slotted-foil emittance spoiling scheme 42 -have been successfully developed to produce sub-10 fs X-ray pulses. However, until now, there has been no diagnostics reported that can measure the X-ray pulses at a resolution of a few femtoseconds or better.…”
Section: Article Nature Communications | Doi: 101038/ncomms4762mentioning
confidence: 99%